Mind Mapping And Brainstorming Strategies In Students’ Writing With High And Low Interest - Ernidawati, Ernidawati; Sutopo, Djoko (English Education Journal, 2017)
This research was aimed to analyze the effectiveness of Mind Mapping and Brainstorming Strategies in teaching writing hortatory exposition text to students with high and low interest. The subject of the study were the eleventh graders of SMK Kesehatan Darussalam Semarang in the academic year of 2016/2017. Two of nine classes in the school were chosen as the samples of the study. This study used experimental research design with factorial design 2x2. The researcher collected and analyzed the data by using questionnaire and writing test. The finding of this research indicates that mind mapping and brainstorming strategies are effective in teaching writing to the students with high and low interest. The result showed that the score of mind mapping strategy was higher than brainstorming strategy. It can be concluded that mind mapping strategy was more effective than brainstorming strategy and there was no interaction among the strategies, writing skill, and interest. It is hoped that the students and the teacher can use those strategies in teaching and learning process.